Urban Development and Rural Poverty in Java: A Challenge for Decentralized Local Government - Salim, Wilmar (Center for Research and Community Services ITB, 2005)
The Government of Indonesia has pursued the strategy of dispersed development to address the issue of environmental degradation, to reduce the concentration of development in one major center, in order to achieve a sustainable urban form. The effectiveness of this strategy is being questioned, since the “deconcentration” of development fails to achieve its objective due to the absence of sound implementation tools and the market forces. The expansion of urban areas not only has characterized the development of Java in the last couple decades, bitt at the same time the decrease of rural areas and rural lives are also taking place, that spurs the physical integration process of major urban centers, especially on the northern coast of Java. The consequence of this process to the larger area, that is the rural hinterland, highlights the mega urban region hypothesis. Meanwhile, the issue of poverty also highlights the condition of rural Java, where spatially it has corresponding patterns with the formation of extended metropolitan regions. Recognizing the dual ism of development trajectory and the uneven spatial distribution of development in Java, this paper would argue that the focus of local government policies ought to be directed towards the promotion of rural regional development in order to achieve a balanced development towards its lagging regions. A new strategy needs to be invented along with its implementation framework, with a goal to achieve sustainability in both urban and rural areas. The new form of decentralized local governments could be the basis for promoting the regional network strategy as the framework for sustainable regional development.Keywords: decentralization policy, urban development, rural poverty